2014
DOI: 10.1093/jmcb/mju005
|View full text |Cite
|
Sign up to set email alerts
|

TRIM4 modulates type I interferon induction and cellular antiviral response by targeting RIG-I for K63-linked ubiquitination

Abstract: RIG-I is a pivotal cytoplasmic sensor that recognizes different species of viral RNAs. This recognition leads to activation of the transcription factors NF-κB and IRF3, which collaborate to induce type I interferons (IFNs) and innate antiviral response. In this study, we identified the TRIM family protein TRIM4 as a positive regulator of RIG-I-mediated IFN induction. Overexpression of TRIM4 potentiated virus-triggered activation of IRF3 and NF-κB, as well as IFN-β induction, whereas knockdown of TRIM4 had oppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
163
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(173 citation statements)
references
References 29 publications
4
163
1
1
Order By: Relevance
“…Overexpression of TRIM4 led to increased IFN induction following infection with Sendai virus (SeV), a paramyxovirus known to be detected by RIG-I [74]. More detailed analysis indicated that TRIM4 interacted with RIG-I and led to the K63-linked ubiquitination of K154, K164, and K172 in the CARDs.…”
Section: The Role Of Ubiquitin In Rlr Signal Transductionmentioning
confidence: 99%
“…Overexpression of TRIM4 led to increased IFN induction following infection with Sendai virus (SeV), a paramyxovirus known to be detected by RIG-I [74]. More detailed analysis indicated that TRIM4 interacted with RIG-I and led to the K63-linked ubiquitination of K154, K164, and K172 in the CARDs.…”
Section: The Role Of Ubiquitin In Rlr Signal Transductionmentioning
confidence: 99%
“…Quantitative real-time PCR (qPCR) assays were performed as previously described (26)(27)(28)(29). Total RNA from mouse or human cells was isolated using TRIzol reagent (Invitrogen).…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
“…Accumulating evidence suggests that many TRIM proteins are involved in antiviral immunity. For example, TRIM4 and TRIM25 regulate the ubiquitination of RIG-I to promote type I IFN production and NF-κB activity [20,21]. Furthermore, TRIM32 and TRIM56 positively regulate DNA virus-induced type I IFN signaling by interacting with STING and targeting it for K63-linked ubiquitination [22,23].…”
Section: Introductionmentioning
confidence: 99%